The Influence of External Factors on Variations in the Length of Nurses' Actions in Clarifying Patient Emergencies in Hospital Emergency Rooms - Yahya, Amriyanti (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
This study aims to analyze the influence of external factors, namely the availability of facilities, training, and consultation/guidance on the variation in the length of time for nurses' actions in clarifying patient emergencies in the Emergency Department (IGD) of a Hospital. This study uses a quantitative design with a cross-sectional approach and Chi Square statistical analysis to test the relationship between these external factors and the variation in the length of time for nurses' actions. Data were collected through questionnaires filled out by respondents, which measured their perceptions of the availability of facilities, training, and consultation/guidance available, as well as the time needed to clarify emergencies. The results of the study showed a significant influence between the availability of facilities, training, and consultation/guidance on the variation in the length of time for nurses' actions in clarifying patient emergencies (p <0.05). This study concludes that these external factors affect the efficiency of nurses' actions in the ER, which has implications for improving the quality of emergency services. Therefore, hospitals need to pay attention to the availability of facilities, training, and consultation/guidance in order to improve nurse performance in handling patient emergencies.